As máquinas podem cuidar? - Eros Carvalho (O Que Nos Faz Pensar)
Applications and devices of artificial intelligence are increasingly common in the healthcare field. Robots fulfilling some caregiving functions are not a distant future. In this scenario, we must ask ourselves if it is possible for machines to care to the extent of completely replacing human care and if such replacement, if possible, is desirable. In this paper, I argue that caregiving requires know-how permeated by affectivity that is far from being achieved by currently available machines. I also maintain that the complete substitution of human caregiving by machine caregiving is not desirable because caregiving requires genuine human connection.